Phnomenological Analysis of Understanding Insurance as Risk Management of Failure Harvesting Shallots in Nganjuk - Intan Puspitasari; Basuki Rahmat (CV Pena Jaya Pers, 2024)
This research was conducted to understand the extent of understanding of financial literacy, especially agricultural insurance for shallot farmers as a way to manage the risk of crop failure. Insurance, as one of the important guarantees owned by farmers, is able to provide encouragement so that conditions such as crop failure and other risks of loss, such as falling prices, can strengthen sustainable shallot production as a promising economic sector in the Nganjuk area. This research uses a phenomenological approach to understand and compile statements from sources regarding understanding agricultural insurance as a risk management need for agricultural production of shallots. The conclusion of this research provides an understanding that farmers need to have and understand insurance to be able to manage shallot production sustainably. Minimizing the risk of loss due to crop failure by using agricultural insurance is highly recommended because agricultural production based on rice fields is very vulnerable to the risk of bad weather, pests, and price declines due to demand and supply factors in the market.